Simulated digestion and in vitro fermentation of a polysaccharide from lotus (Nelumbo nucifera Gaertn.) root residue by the human gut microbiota. (May 2022) - Guan, Xueting; Feng, Yujing; Jiang, Yunyao; Hu, Yeye; Zhang, Ji; Li, Zhengpeng; Song, Chao; Li, Fu; Hou, Jincai; Shen, Ting; Hu, Weicheng
Graphical abstract: Highlights: Lotus root polysaccharide (LRP) could be partially degraded during simulated digestion in vitro . LRP could be degraded and utilized by gut microbiota. LRP could decrease intestinal pH and promote the production of short-chain fatty acids. LRP improved the structure and composition of gut microbiota. Abstract: Lotus root polysaccharide (LRP) is an active water-soluble polysaccharide with average molecular weight of 1.24 × 10 4 . It was composed of (1 → 4)-α-D-glucan backbone with α-D-glycopyranosyl moieties connected to C-6 positions of the glucose residues as side chains approximately every six residues. However, little information is available for its digestion and fermentation characteristics in vitro . The results showed that the levels of reducing sugars were increased slightly, and the molecular weight was also reduced slightly, in simulated gastric and small intestinal juices. During in vitro fermentation, the total sugar, reducing sugar and glucose contents decreased gradually with increasing fermentation time. The molecular of LRP was degraded and to metabolize into a variety the short-chain fatty acids (SCFAs) such as acetic, propionic, and butyric acids. Furthermore, LRP fermentation decreased the pH of the fermentation broth and increased its absorbance. Meanwhile, LRP modulated the gut microbiota by altering the Firmicutes / Bacteroidetes ratio and increasing the relative abundance of Bifidobacterium . The findings from this study showed that LRP could be developed as potential prebiotic to regulate the composition of gut microbiota, thereby promote the production of SCFAs.